EVALUASI IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA (K3) MENGGUNAKAN MODEL KIRKPATRICK (JPMPPI (Jurnal Pengabdian Masyarakat), 2023)
The purpose of this community service activity is to improve student skills relatedto the application of occupational safety and health in the field of weldingengineering. Implementation activities are carried out using face-to-facemethods, simulations and direct field work practices. This activity was attendedby 24 participants from Vocational High Schools (SMK). The activity was carriedout at the Madiun Indonesian Railways Polytechnic Workshop and Workshopand BLK. Evaluation of learning activities is carried out using the Kirkpatrick FourLevel method. The results of this activity can increase participants'understanding of welding safety and health. Keywords: Occupational Health & Safety, Welding, Kirkpatrick Four Levels